Effects of music on task performance, engagement, and behavior: A literature review. (September 2017) - Schwartz, Rachel W.; Ayres, Kevin M.; Douglas, Karen H.
Currently, there is a growing body of empirical research regarding the role of background music in the education of individuals with disabilities. A systematic literature review identified 20 studies between 1970 and 2014 focusing on the role of contingent and noncontingent background music to facilitate task engagement, enhance performance, and alter behavior. Though the research addressing background music has mixed results, there is evidence suggesting that this could be an effective strategy for increasing task engagement and performance and decreasing stimulatory behavior for individuals with developmental disabilities. Since music can be considered inexpensive and may be less intrusive in comparison to other strategies, its use merits additional study to explore how and to what extent music affects behavior.